Pengaruh Intensitas Penggunaan Smartphone Terhadap Pola Perilaku Siswa di SMAN 7 Medan - Eni Meliani Sipayung; Lasma Siagian; Nova Yunita Sari (Visi Sosial Humaniora, 2026)
The rapid development of digital technology has led to an increase in smartphone use among students. However, uncontrolled smartphone use can affect students' behavior patterns in their daily lives and in their learning activities at school. Previous studies have focused more on smartphone use in general, so more specific studies are needed on the effect of smartphone use intensity on student behavior patterns in the school environment. This study aims to determine the effect of smartphone usage intensity on student behavior patterns at SMAN 7 Medan. This study uses a quantitative approach with a correlational method. The population in this study was all 360 students in grade XI at SMAN 7 Medan in the 2026/2027 academic year. A sample of 80 students was taken using cluster sampling. The data collection instrument used a questionnaire with a Likert scale that had been tested for validity and reliability. Data analysis was performed through normality tests, linearity tests, and simple linear regression analysis using SPSS version 26. The results showed that there was a significant effect between the intensity of smartphone use and student behavior patterns. This is evidenced by a t-value of 5.977, which is greater than the t-table value of 1.991 (5.977 > 1.991) with a significance value of 0.000 < 0.05. The F-test results also show The F-value is 35.727 with a significance of 0.000 < 0.05, so the regression model is significant. The coefficient of determination (R Square) value of 0.314 shows that 31.4% of the variation in student behavior patterns is influenced by the intensity of smartphone use, while 68.6% is influenced by other factors outside the scope of this study.